A new genus and species of Laelapidae Canestrini from Sri Lanka (Acari: Mesostigmata) - Joharchi, Omid; Halliday, Bruce (Zootaxa, 2021)
We describe a new monotypic genus in the mite family Laelapidae, Hyposternus gen. nov., to accommodate a new species, H. ceylonicus sp. nov., on the basis of female, male and protonymph specimens collected from soil-litter in Sri Lanka. The female of the new genus differs from other genera of Laelapidae by having a strongly desclerotised sternal shield, essentially represented by a narrow anterior and lateral sclerotised ridges. Other distinctive features of the new species include the absence of dorsal shield seta z3, an epistome projecting anteriorly, movable digit of the chelicera tapered apically, an elongate anal shield, thorn-like opisthogastric setae, an anteriorly widened hypostomal groove, and long dorsal macrosetae ad1 on femora II–IV.